2010
DOI: 10.1111/j.1537-2995.2009.02545.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin M red blood cell alloantibodies are frequently adsorbed by rabbit erythrocyte stroma

Abstract: BACKGROUND: Rabbit erythrocyte stroma (RESt, Immucor) adsorption is often used to remove cold autoantibodies from patient samples to facilitate detection of underlying alloantibodies. However, reports in the literature show that adsorption of clinically significant alloantibodies can occur. A 2006 study by Storry and colleagues suggested that immunoglobulin (Ig)M antibodies are adsorbed by RESt regardless of antigen specificity. In our study, we further investigated the adsorption of IgM red blood cell alloant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…5 Rabbit erythrocyte stroma-adsorbed plasma should not be used to determine reverse ABO group as anti-B, in addition to other RBC alloantibodies, can be removed during the adsorption process. 17…”
Section: Resultsmentioning
confidence: 99%
“…5 Rabbit erythrocyte stroma-adsorbed plasma should not be used to determine reverse ABO group as anti-B, in addition to other RBC alloantibodies, can be removed during the adsorption process. 17…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that these reagents may variably adsorb IgM alloantibodies. 7 For these reasons, the rabbit RBC/stroma-adsorbed plasma/serum should not be used for testing performed at immediate spin, for ABO reverse typing, or for compatibility testing. Moreover, some alloantibodies, such as anti-D, anti-E, and anti-Le b have been shown to be reduced in titer strength or even completely adsorbed by these methods.…”
Section: Methodsmentioning
confidence: 99%